Clinical, Radiometabolic and Immunologic Effects of Olaparib in Locally Advanced Triple Negative Breast Cancer: The OLTRE Window of Opportunity Trial - Schettini, Francesco; Corona, Silvia Paola; Giudici, Fabiola; Strina, Carla; Sirico, Marianna; Bernocchi, Ottavia; Milani, Manuela; Ziglioli, Nicoletta; Aguggini, Sergio; Azzini, Carlo; Barbieri, Giuseppina; Cervoni, Valeria; et al. (Frontiers in Oncology, 2021)
Introduction: Olaparib is effective in metastatic triple negative breast cancer (TNBC) carrying germline mutations in DNA damage repair (DDR) genes BRCA1/2 (gBRCA-mut). The OLTRE window-of-opportunity trial preliminarily investigated potential pathologic, radiometabolic and immune biomarkers of early-response to olaparib in gBRCA-wild-type (wt) TNBC and, as proof-of-concept in gBRCA-mut HER2-negative BC. Methods: Patients received olaparib for 3 weeks (3w) before standard neoadjuvant chemotherapy and underwent multiple FDG18-PET/CT scan (basal, after olaparib), clinical assessments (basal, every 3w), tumor biopsies and blood samplings (baseline, after olaparib). Clinical and radiometabolic responses were evaluated according to RECIST1.1 and PERCIST criteria. Results: 27 patients with gBRCA-wt TNBC and 8 with gBRCA-mut BC (6 TNBC, 2 HR+/HER2-negative) were enrolled. Three (11.1%) patients showed mutations in non-BRCA1/2 DDR genes and 4 (14.8%) in other genes. 3w olaparib induced 16/35 and 15/27 partial clinical and radiometabolic responses, including in 40.7% and 50.0% gBRCA-wt patients. gBRCA-mut tumors presented numerically higher tumor-infiltrating lymphocytes (TILs) levels and PD-L1 positive tumors. Clinical responders experienced a reduction in T-regs/T-eff ratio (p=0.05), B and NK lymphocytes (p=0.003 both), with an average increase in T-helpers rate (p<0.001) and CD4/CD8 ratio (p=0.02). Ki67% and TILs did not vary significantly (p=0.67 and p=0.77). A numerical increase in PD-L1 positive cases after olaparib was observed, though non-significant (p=0.134). No differences were observed according to gBRCA status and type of response. Conclusions: Early-stage TNBC might be a target population for olaparib, irrespective of gBRCA mutations. Future trials should combine TILs, PD-L1 and gBRCA status to better identify candidates for escalated/de-escalated treatment strategies including olaparib.